Analysis of the Effects of Employee Creativity Antecedents and Organizational Innovation with Initiative Culture as a Moderating Variable (Study on Employees of BPJS Kesehatan) - Sari Verdiana, Antokalina (Syntax Literate, 2026)
The underlying motivation for innovation in public sector organizations is to improve service and problem-solving. Creativity can be considered an important prerequisite for organizational innovation. This research is quantitative confirmatory, which aims to analyze the influence of employee creativity (knowledge sharing, person-organization fit, and business ethics) on organizational innovation with friendly-initiative culture as a mediating variable. Data collection in this study used non-probability sampling with a purposive sampling technique, with a total sample of 530 employees from the BPJS Kesehatan Head Office and six Regional Deputies who had been working for more than one year. Questionnaires were distributed online using the www.surveymonkey.com application. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS® version 3.2.8. The results showed that business ethics significantly influenced employee creativity, which in turn impacted organizational innovation, whereas knowledge sharing, person-organization fit, and initiative-friendly culture did not demonstrate significant effects in this research model.